Review on COx-free hydrogen from methane cracking: Catalysts, solar energy integration and applications - Aliya Banu (17017731) (2021)
Hydrogen fuel production from methane cracking is a sustainable process compared to the ones currently in practice due to minimal greenhouse gas emissions. Carbon black that is co-produced is a valuable product and can be marketed to other industries. As this is a high-temperature process, using concentrated solar energy can further improve its sustainability. In this study, a detailed review is conducted to study the advancements in methane cracking for hydrogen production using different catalysts. Various solar reactors developed for methane cracking are discussed. The application of hydrogen to produce other valuable chemicals are outlined. Hydrogen carriers such as methanol, dimethyl ether, ammonia, and urea can efficiently store hydrogen energy and enable easier transportation. Further research in the field of methane cracking is required for reactor scale-up, improved economics, and to reduce the problems arising from carbon deposition leading to reactor clogging and catalyst deactivation. Other Information Published in: Energy Conversion and Management: X License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ecmx.2021.100117